Prospects for sustainable development of the digital economy in the region - Amirkulov Olimjon Adham ugli (THE INNOVATION ECONOMY, 2026)
The article discusses the issues of sustainable development of the digital economy in the region. In particular, it analyzes the impact of the introduction of digital technologies on the regional economy, the significance of e-government, e-commerce, and the digital financial system. Furthermore, the prospects for improving digital infrastructure, human capital, and the investment environment are scientifically substantiated. The research employs statistical and comparative analysis methods and identifies priority areas of digital transformation in ensuring regional economic sustainability.